Consumer behavior and awareness regarding products for food hypersensitivity: trends, motivations, and educational gaps - Kiciak, Agata; Kołodziejczyk, Aleksandra; Kuczka, Natalia; Łokaj, Paulina; Staśkiewicz-Bartecka, Wiktoria; Białek-Dratwa, Agnieszka; Bielaszka, Agnieszka; Dobkowska-Szefer, Daria; Kowalski, Oskar; Kardas, Marek (Frontiers in Nutrition, 2025)
Background/ObjectivesFood hypersensitivity, including allergies and intolerances, represents a significant and growing health challenge. To address this issue effectively, it is essential to implement tailored dietary interventions that can effectively reduce symptoms and improve patients' quality of life. The study aimed to analyze the consumption of specialist products intended for people with food hypersensitivities and to assess knowledge of food allergies and food intolerances.MethodsThe study was conducted from January to May 2021 using an original survey questionnaire that was made available to respondents in electronic form. The study involved 191 people, including 132 women and 59 men.ResultsThe analysis showed that the knowledge of respondents about the labeling of products dedicated to people with food allergies and intolerances was generally satisfactory, but significant gaps were found in the knowledge of less common allergens, such as histamine or egg white. In addition, the consumption of products dedicated to food allergies and intolerances was comparable in the groups of diagnosed and healthy people.ConclusionsAlthough the general knowledge of consumers about product labels was high, there are significant gaps in knowledge of more specific allergens. Moreover, the results suggest that products dedicated to people with food allergies and intolerances are consumed by both healthy and diagnosed people, which indicates the need for further education in this area.